Effects of fasting during Ramadan month on depression, anxiety and stress and cognition - Amin, Arati; Kumar Sai, Sailesh; Mishra, Soumya; Kumar Reddy, Udaya; N., Sriram; Mukkadan, J K (International Journal of Medical Research and Review, 2016)
Objective: The present study was aimed to observe the effect of fasting during the Ramadan month on depression, anxiety and stress scores. Materials and Methods: Twenty healthy male Muslim students of Little Flower Institute of Medical sciences and Research, with previous fasting experience during Ramadan were selected for the present study by convenience sampling method. Depression, anxiety and stress scale (DASS 42) was used to assess depression, anxiety and stress. MMSE (Mini Mental State Examination) was used to assess cognition. Results: Depression, anxiety scores significantly decreased on 14th and 28th day when compared with baseline values. Stress scores were decreased significantly on 28th day. Cognition levels were significantly improved followed by fasting in 14th day and 28th day. Conclusion: In the present study, we have observed positive impact of fasting on depression, anxiety and stress scores and cognitive functions. We recommend further detailed studies including male and female participants and biochemical parameters to investigate other aspects of Ramadan fasting on human stress and cognition.